Environmental Printing Level Differences between Four Years Old and Five Years Old Children: Perbezaan tahap Pencapaian Cetakan Persekitaran antara Kanak-Kanak berumur Empat Tahun dengan Kanak-Kanak berumur Lima Tahun - Nor Azman, Amirul Azwan bin (Jurnal Pendidikan Bitara UPSI, 2022)
This study was conducted to identify differences in the level of achievement of environmental print recognition between four years old and five years old. Therefore, this study was conducted based on three objectives, namely to identify the level of achievement of the four-year and fiveyear environmental prints. At the same time, the researcher will also look at the differences in the level of environmental print achievement involving the two ages of the child. The study design used is quantitative in the form of a survey. The sample involved in this study was a total of 60 children of which 30 children were 4-year-olds and the rest were 5-year-olds. This sample was taken from children who received kindergarten education around Tanjong Malim area. The instrument used in the implementation of the study is an environmental print test. The results of the study showed that the level of environmental print achievement of 4-years old children is good with the total mean score obtained by 4-year-olds is 12.27 while the level of environmental print achievement of 5-year-old children shows that they are at a good level with total mean score 14.03. Furthermore, the difference in the level of environmental print achievement between children aged 4 and 5 years is not significant. This is obtained as a result of the mean score for both ages of the child recorded a mean of 11-15 mean score based on table 4.2 and both are at a good level. However, the mean score recorded by 5-years old was higher than 4-years old. This indicates that the results of the alternative hypothesis are insignificant but have differences based on the overall mean score.